Circular Hough Transform to improve viable Saccharomyces cerevisiae identification - Borges, Felipe Silveira Brito; Silva, Diogo Soares da; Quinta, Lia Nara Balta; Mongelo, Arnaldo Ibanhe; Cereda, Marney Pascoli; Pistori, Hemerson (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão ComputacionalDO - 10.5753/wvc.2021.18895, 2021)
Yeast counting is an important step in monitoring the fermentation process in sugarcane mills to optimize ethanol production. There is a need for a faster method to count viable cells in place of the fastidious and operator-dependent traditional method. In this paper, the application of a slightly modified version of the standard Circular Hough Transforms to automate the inoculated fermentation process of Saccharomyces cerevisae is reported. The results of several experiments with different preprocessing algorithms and parameter adjustments are presented. The resulting system will be part of a microbiological control procedure that is being developed to respond to Brazilian ethanol sugarcane mill's demands.